2023
DOI: 10.1002/mgg3.2163
|View full text |Cite
|
Sign up to set email alerts
|

New insights from trio whole‐exome sequencing in the children with kidney disease: A single‐center retrospective cohort study

Abstract: Background Kidney disease of children markedly affects their health and development. Limited clinical data of early‐stage kidney disease render a tremendous challenge for the accurate diagnosis. Trio whole‐exome sequencing (Trio‐WES) is emerging as a first‐line diagnostic strategy in pediatric kidney disease, and shows important implications for the precision medicine strategies of children with kidney disease. Methods Trio‐WES was performed in 133 Chinese children with kidney disease and their parents. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The corresponding diagnostic yield for non-specific CKD clinical presentations range from 32 to 52% for pediatric cases [45][46][47][48], 30 to 51% for pediatric/adult [49][50][51][52] and 9.3 to 34% for adult cases [53,54,63].…”
Section: Whole-exome Sequencingmentioning
confidence: 99%
“…The corresponding diagnostic yield for non-specific CKD clinical presentations range from 32 to 52% for pediatric cases [45][46][47][48], 30 to 51% for pediatric/adult [49][50][51][52] and 9.3 to 34% for adult cases [53,54,63].…”
Section: Whole-exome Sequencingmentioning
confidence: 99%
“…Chen et al reported 44.74% for isolated hematuria, 59.62% for proteinuria and hematuria, 50% for simple proteinuria, 50% for renal insufficiency, and 54.55% for others. The mutated genes observed were ACE, ADCK4, COL4A4, COL4A5, CLCN5, PKD1, and SMARCAL1[9]. The diagnostic yield for the Bekheirnia et al study showed 42% for CAKUT, 79% for cystic kidney disease, 70% for proteinuria, and 67% for hematuria, and the observed mutated genes were COL4A4, HNF1B, PKD1, PKHD1, and WT1[10].…”
mentioning
confidence: 92%
“…Huang et al reported 40.6% cases of nephrolithiasis, 40.6% of nephrocalcinosis, and 18.8% cases of nephrolithiasis+nephrocalcinosis with the highest total diagnostic yield of 78.1% among the included studies[8], followed by Chen et al, who reported a total diagnostic yield of 52%, while the spectrum of kidney diseases showed 28.87% cases of isolated hematuria, 39.1% of proteinuria and hematuria, 10.53% of simple proteinuria, 13.53% of renal insufficiency, and 8.27% of others[9]. Bekheirnia et al stated quite a closer total diagnostic yield of 51% with 26% cases of cystic kidney disease, 21% of congenital anomalies of the kidneys and urinary tracts (CAKUT), 20% of hematuria, and 11% of proteinuria[10].Rao et al reported 55.3% of cases of glomerular disease; CAKUT accounted for 15.9% of cases; 8.3% of cystic renal disease; 15.9% of renal tubular disease and renal calcinosis or nephrolithiasis; and 4.6% of CKD 3-5 stages, while the total diagnostic yield was 42.10%[11].…”
mentioning
confidence: 92%
“…Genetic indicators are objective microscopic information that is extremely valuable for precise, objective diagnosis of diseases [ 19 ]. Relevant studies have shown that there were differences in gene expression between YinDC and balanced constitution (BC) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%